KAMPUNG NU SEBAGAI ARENA KUASA: PEMBERDAYAAN DAN OTORITAS LOKAL DI DESA BENELAN LOR KECAMATAN KABAT-BANYYUWANGI - MUHAMMAD SAHLAN (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
This study analyzes Kampung NU as an arena of power by examining the interplay between community empowerment and local authority in Benelan Lor Village. Kampung NU has emerged as a community-based religious initiative that intersects with village governance, religious identity, and grassroots participation. The objective of this research is to explore how Kampung NU operates not only as a mechanism for social empowerment but also as a space where power relations among village officials, Nahdlatul Ulama (NU) grassroots elites, and local communities are constructed and negotiated. This research employs a qualitative case study approach. Data were collected through in-depth interviews, participant observation, document analysis, and supported by preliminary survey data. The findings indicate that Kampung NU performs a dual function: strengthening religious identity and social cohesion while simultaneously serving as an instrument of symbolic and structural power for local elites. Empowerment narratives are predominantly framed through dominant religious discourse, influencing participation patterns and authority distribution at the village level. The study concludes that Kampung NU represents a dialectical space where empowerment and power coexist, revealing the complexity of religion-based community development in rural Indonesia.